2021
DOI: 10.1371/journal.pone.0246925
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal scaling analyses of urban street network structure: The cases of twelve megacities in China

Abstract: Traffic networks have been proved to be fractal systems. However, previous studies mainly focused on monofractal networks, while complex systems are of multifractal structure. This paper is devoted to exploring the general regularities of multifractal scaling processes in the street network of 12 Chinese cities. The city clustering algorithm is employed to identify urban boundaries for defining comparable study areas; box-counting method and the direct determination method are utilized to extract spatial data;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…A variety of parameter estimation methods exist, including the ordinary least squares method (OLS), maximum likelihood method (MLM), etc. [ 28 ]. In this paper, we have chosen to use OLS and fix the intercept at 0 during regression [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of parameter estimation methods exist, including the ordinary least squares method (OLS), maximum likelihood method (MLM), etc. [ 28 ]. In this paper, we have chosen to use OLS and fix the intercept at 0 during regression [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the spatial level, the spectra under positive moment orders correspond to central or high-density areas in a city, while those under negative moment orders correspond to marginal or low-density areas [ 17 ]. It has been observed that the spectra under positive moment orders exhibit similarities across different cities, while the spectra under negative moment orders display significant variations between cities [ 28 , 29 ]. This distinct growth pattern of spectra suggests that central areas represent stable zones for urban development, while marginal areas are the most dynamic regions for urban growth.…”
Section: Introductionmentioning
confidence: 99%
“…As paths got reinforced and cities evolved, the process took place in a non-uniform way, leading to different growth rates in the system. This produced a multifractal organisation of the street network [ 85 , 86 ], and of urban systems in general [ 87 ]. The self-organised processes, together with top-down interventions are responsible of the observed morphologies of cities.…”
Section: Morphology and Inequalitymentioning
confidence: 99%
“…An FD-calculating module is embedded in some common GIS software, including SpaDiS, Exeter GS, Geostat Office, etc. [30]. In the present study, Benoit software was employed.…”
Section: Introductionmentioning
confidence: 99%